Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex - Fischbach, Robert Josef; Staudt, Michael; Zimmer, Ina; Rambal, Serge; Schnitzler, Jörg-Peter (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers accession-num: 12060257
Keywords: monoterpene emissions; monoterpene synthase activities; Quercus ilex; seasonal patterns (voyant)